2010
DOI: 10.1111/j.1740-8709.2010.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake misreporting among children and adolescents: a literature review

Abstract: While adults' energy intake misreporting is a well-documented phenomenon, relatively little is known about the nature and extent of misreporting among children and adolescents. Children's and adolescents' dietary reporting patterns are likely to be distinct because of their ongoing cognitive and social development. These developmental differences present unique challenges to aspects of dietary reporting, such as food knowledge, portion size estimation and response editing. This review of 28 articles describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 45 publications
9
118
2
3
Order By: Relevance
“…Finally, the BMI-for-age z scores suggested that the children were, on average, heavier than the American reference population, one of the many variables known to be associated with underreporting. [34][35][36][37] Against the backdrop of limited testeretest reliability of the modified MEDFICTS in the group as a whole and specifically among boys the lack of significant correlations between the final score in the modified MEDFICTS and the PFE, PSFE, and cholesterol in the food records was not surprising. Thus, only for girls could a meaningful relative validity be reasonably expected.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the BMI-for-age z scores suggested that the children were, on average, heavier than the American reference population, one of the many variables known to be associated with underreporting. [34][35][36][37] Against the backdrop of limited testeretest reliability of the modified MEDFICTS in the group as a whole and specifically among boys the lack of significant correlations between the final score in the modified MEDFICTS and the PFE, PSFE, and cholesterol in the food records was not surprising. Thus, only for girls could a meaningful relative validity be reasonably expected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a majority of self-reported energy intake data from the National Health and Nutrition Examination Survey (NHANES) are not physiologically plausible (Archer, Hand, & Blair, 2013). Moreover, there are examples of both under-and over-reporting across other studies that use self-reported energy intake, particularly in children and adolescents (Fisher, Johnson, Lindquist, Birch, & Goran, 2000;Forrestal, 2011;Santos, Pascoal, Fisberg, Cintra, & Martini, 2010). Heavier youth are more likely to underreport the amount they eat on self-report measures compared to their actual intake (Wolkoff et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…33 In 2015, a multi-national report demonstrated that misreporting “ in five populations of the African diaspora ” 81 was substantial with the South African cohort exhibiting an astounding 52.1% underreporting of dietary energy intake. 81 With respect to age, Forrestal (2011) found in children and adolescents that misreporting “…appeared to be more common than it is among adults .” 82 The ubiquitous nature of misreporting and the consistency of research results over many decades and across multiple populations, cohorts, and countries provide strong support that M-BM measures of EI are fatally flawed and therefore, diet-health inferences from studies that use M-BM are essentially meaningless.…”
Section: The Memory-based Methods Of Nutrition Epidemiologymentioning
confidence: 99%